2022
DOI: 10.1101/2022.11.04.515251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of the cerebellum in learning to predict reward: evidence from cerebellar ataxia

Abstract: Recent findings in animals have challenged the traditional view of the cerebellum solely as the site of motor control, suggesting that the cerebellum may also be important for learning to predict reward from trial-and-error feedback. Yet, evidence for the role of the cerebellum in reward learning in humans is lacking. Moreover, open questions remain about which specific aspects of reward learning the cerebellum may contribute to. Here we address this gap through an investigation of multiple forms of reward lea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…By extension, the specific cerebellar microzones involved in implicit reach adaptation may be insensitive to reward, despite the fact that reward may play a role in tasks dependent on other cerebellar circuits and the popular presupposition of a single cerebellar computation (Diedrichsen et al 2019; Kostadinov and Häusser 2022). Indeed, the idea that cerebellar circuits for implicit motor learning and reward processing are divided is supported by observations that patients with cerebellar degeneration can engage in many aspects of typical reward-driven reinforcement learning despite showing substantial deficits in adaptation (Morehead et al 2017; Nicholas et al 2022; Therrien et al 2016). Such a division of reward-based and sensory prediction error-based learning would be consistent with classical observations of differences between sensory-prediction error-based supervised motor learning and reinforcement learning (for review see Gershman and Uchida 2019; Raymond and Medina 2018).…”
Section: Discussionmentioning
confidence: 99%
“…By extension, the specific cerebellar microzones involved in implicit reach adaptation may be insensitive to reward, despite the fact that reward may play a role in tasks dependent on other cerebellar circuits and the popular presupposition of a single cerebellar computation (Diedrichsen et al 2019; Kostadinov and Häusser 2022). Indeed, the idea that cerebellar circuits for implicit motor learning and reward processing are divided is supported by observations that patients with cerebellar degeneration can engage in many aspects of typical reward-driven reinforcement learning despite showing substantial deficits in adaptation (Morehead et al 2017; Nicholas et al 2022; Therrien et al 2016). Such a division of reward-based and sensory prediction error-based learning would be consistent with classical observations of differences between sensory-prediction error-based supervised motor learning and reinforcement learning (for review see Gershman and Uchida 2019; Raymond and Medina 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is evidence from studies of animal models that the cerebellum encodes information about appetitive and social rewards [54][55][56][57]. Studies in humans have also shown that cerebellar damage can disrupt learning from monetary rewards in non-motor tasks [58][59][60]. However, important differences exist between the cerebellar encoding of reward and the canonical reward encoding in midbrain dopaminergic neurons [54,61].…”
Section: Discussionmentioning
confidence: 99%